2018
DOI: 10.1108/ecam-02-2017-0036
|View full text |Cite
|
Sign up to set email alerts
|

An empirical investigation of the learning effect in concrete operations

Abstract: Purpose The purpose of this paper is to focus on productivity as it unfolds during the execution of a particular task, i.e., reinforced concrete operations. The main aim is understanding whether the learning effect explaining the improvement of productivity in subsequent cycles of a given repetitive construction process is mainly attributable to a pure worker learning (independent on the specific site) or to the experience developed by the crew on the site conditions. Design/methodology/approach The authors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 50 publications
(65 reference statements)
1
10
0
3
Order By: Relevance
“…Tendo em vista que a "Produtividade Média" apresentou as melhores condições de ajuste, se avaliou o efeito da aprendizagem com base neste indicador. Assim, se observou, nas duas faixas de diâmetro, que não se houve melhoria da "Produtividade Média", o que está em desacordo com a literatura, tanto para a soldagem, quanto para outras atividades da indústria da construção (Ammar & Samy, 2015;Anzanello, 2004;Cadaval Júnior et al, 2013;(Pellegrino et al, 2012;Jarkas, 2016;(Pellegrino & Constantino, 2018;Raman & Varghese, 2016;Srour et al, 2016;Ralli et al, 2020). A melhoria da produtividade a partir do 10 o dia não se verificou (Martins, 2011;PROMINP, 2009).…”
Section: -Efeito Da Aprendizagem Na Produtividadeunclassified
See 2 more Smart Citations
“…Tendo em vista que a "Produtividade Média" apresentou as melhores condições de ajuste, se avaliou o efeito da aprendizagem com base neste indicador. Assim, se observou, nas duas faixas de diâmetro, que não se houve melhoria da "Produtividade Média", o que está em desacordo com a literatura, tanto para a soldagem, quanto para outras atividades da indústria da construção (Ammar & Samy, 2015;Anzanello, 2004;Cadaval Júnior et al, 2013;(Pellegrino et al, 2012;Jarkas, 2016;(Pellegrino & Constantino, 2018;Raman & Varghese, 2016;Srour et al, 2016;Ralli et al, 2020). A melhoria da produtividade a partir do 10 o dia não se verificou (Martins, 2011;PROMINP, 2009).…”
Section: -Efeito Da Aprendizagem Na Produtividadeunclassified
“…A melhoria da produtividade a partir do 10 o dia não se verificou (Martins, 2011;PROMINP, 2009). Esperava-se que esta melhora viesse a ocorrer, ao menos, em função da aclimatação dos trabalhadores às condições do local de trabalho (Pellegrino & Constantino, 2018;Ralli et al, 2020). Cabe destacar, que a soldagem das juntas de tubulações são atividades individuais, dependem da habilidade de cada soldador e a amostra estudada considera a média diária dos soldadores e não produto de um trabalho de equipe.…”
Section: -Efeito Da Aprendizagem Na Produtividadeunclassified
See 1 more Smart Citation
“…Therefore, it has been observed that when executing repetitive construction activities (e.g. high-rise building construction) each subsequent production cycle may be improved form a productivity stance due to the learning phenomenon that is developed in relation to the resources that are deployed in the project (Thomas et al, 1986;Panas and Pantouvakis, 2014;Pellegrino and Costantino, 2018;Srour et al, 2018). In other words, the productivity of repetitive tasks is improved as the experience of the deployed crews is increased (Pellegrino et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Taking into account learning phenomena when studying construction productivity enhances the accuracy of time and cost management (Lutz et al, 1994;Ammar and Abdel-Maged, 2018), improves project control and programming (Pellegrino et al, 2012), as well as provides the required scientific evidence for claiming lost workhours (Thomas, 2009). The impact of the learning effect on labor productivity is graphically expressed by the learning curves, which are quantitatively analyzed by mathematical models (Pellegrino and Costantino, 2018) known as the learning curve models.…”
Section: Introductionmentioning
confidence: 99%